Strategi Internalisasi Nilai-Nilai Islam untuk Membentuk Karakter Jujur dan Disiplin Siswa di Madrasah Ibtidaiyah Nw Tarekat Tahun Pelajaran 2019/2020 - Munawir Gazali (Peneliti.net, 2020)
This study describes the strategy of internalizing Islamic values ​ form students' honest and disciplined character. This study used a descriptive approach, the data were collected from interview, observation and documentation methods. Internalization strategy was conducted by the teacher provides examples to the students related with honest behavior and discipline behavior, provides concepts of honesty and discipline for the students used rules and policies related to honesty and discipline, given advice, provide media, builds approaches with students and communication with parents of students. The steps in internalization start from providing honest and disciplined concepts to students, providing behavior choices and inviting them to behave honestly and disciplined, implementing honest behavior and student discipline. The resulting impact could be change the condition of a more religious school as evidenced by the enthusiasm of students participating in school religious activities and students with more character, including honest character and disciplined character, responsibility, confidence, mutual respect, helpful, careful for cleanliness and beauty. The student achievement has improved both academically and non-academically and public trust in the institution is getting higher. So the internalization of Islamic values ​​is very urgent to be applied in schools to build the honest character and discipline of students.